2017
DOI: 10.1590/0104-07072017002310016
|View full text |Cite
|
Sign up to set email alerts
|

Práticas Das Equipas Na Prevenção De Queda Nos Idosos Institucionalizados: Construção E Validação De Escala

Abstract: Objective: determine and elaborate the psychometric characteristics of nursing team practices and develop a behavior scale for fall risk management in institutionalized elderly people.Method: the scale was designed based on a literature review and observation of the work of the teams in a long-term care institution for the elderly. The content of the scale was analyzed and the concordance index of the 14 initial items was checked by nine experts. The scale was applied to a sample of 152 caregivers from six lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 17 publications
1
25
0
4
Order By: Relevance
“…The multifactorial nature and complexity of the relationship among fall risk factors make it difficult to control this problem. The prevention of falls implies multiprofessional teamwork, with interventions directed by teams that play a crucial role in the implementation of best practices, from risk assessment to implementation of preventive measures and communication of fall episodes (5) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The multifactorial nature and complexity of the relationship among fall risk factors make it difficult to control this problem. The prevention of falls implies multiprofessional teamwork, with interventions directed by teams that play a crucial role in the implementation of best practices, from risk assessment to implementation of preventive measures and communication of fall episodes (5) .…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature showed that there have been recommendations for team interventions and studies that have focused on the development of communication processes and their impact on decreases in prevalence, risk and associated injuries (5)(6)8) . However, there has been no work focused on structured team interventions in order to develop skills in managing the fall risk of the elderly population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations